Characterization of potato genotypes using molecular markers - Collares, Eliana Antonia Silveira; Choer, Eva; Pereira, Arione da Silva (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to characterize 27 potato genotypes, using molecular markers. Polyacrylamide gel electrophoresis, RAPD techniques and isozymes of esterase, phosphoglucomutase and soluble proteins were analyzed in tubers, and isocitrate dehydrogenase, aspartate transaminase, phosphoglucomutase and peroxidase, in leaves. Eighteen primers were tested and four were chosen, kits OPX (01, 04 and 09) and OPY (07), to analyze RAPD markers in leaf extracts. Similarity and cluster analysis were conducted using Jaccard coefficient and the unweighted pair-group method using arithmetic average. Despite the differences detected in the analysis of proteins and isozymes in the tubers, as well as of isozymes in the leaves, the characterization of all genotypes through gel electrophoresis was not possible, while RAPD markers were efficient to characterize all the 27 genotypes.